1996
DOI: 10.1021/jp953740g
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Coefficients of Intrinsically Electroactive Polyelectrolytes and of Counterions Bound to Them

Abstract: An electroactive label was attached to poly(acrylic acid) (molecular weight ) 5000) by reaction with ferrocenylethanol. The resulting ferrocene label was stable when the polymer was dissolved in aqueous solutions, and the diffusion coefficient of the labeled polymer was estimated from the currents obtained as the ferrocene was oxidized at a rotating disk electrode. Although strong adsorption of the polymer on the electrode surfaces depressed the oxidation currents below the convection-diffusion controlled valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Poly(acrylic acid) (PAA) has been used electrochemically for uptake of redox cations, e.g., bis-bipyridyl cobalt [1,2], cadmium in the presence of alumina [3], cupper [4], tris(2,2 0 -bipyridyl)ruthenium [5], nickel(II) tetraazamacrocyclic complex [6], bis-bipyridyl osmium [7], hexaammineruthenium and hexaamminecobalt [8], ferrocenylethanol [9], thallium [10], some alkali metal hydroxides without salts [11], and N,N-dimethylaminomethyl-ferrocene [12]. Negatively charged molecules such as hexacyanoferrate cannot be simply taken up to PAA [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poly(acrylic acid) (PAA) has been used electrochemically for uptake of redox cations, e.g., bis-bipyridyl cobalt [1,2], cadmium in the presence of alumina [3], cupper [4], tris(2,2 0 -bipyridyl)ruthenium [5], nickel(II) tetraazamacrocyclic complex [6], bis-bipyridyl osmium [7], hexaammineruthenium and hexaamminecobalt [8], ferrocenylethanol [9], thallium [10], some alkali metal hydroxides without salts [11], and N,N-dimethylaminomethyl-ferrocene [12]. Negatively charged molecules such as hexacyanoferrate cannot be simply taken up to PAA [5].…”
Section: Introductionmentioning
confidence: 99%
“…The uptake of cations to PAA is caused by association of the carboxyl moiety in PAA, and hence a degree of the uptake should be determined by the pK a as well as pH in solution [5,9], as is predicted from the association in acetic acid. When PAA is in a solid state or a film, the association is complicated by block of a loss of permeation of solvent and ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable interest in the synthesis of new polymers via introducing functional ferrocene derivative structure because of their potential applications in optical, electronic and magnetic materials [1]. However, the reports relating to conductive polymers with ferrocene moiety are scarce.As far as know, most of the known ferrocenyl compounds are only soluble in hydrophobic media that limited their application in aqueous systems [2,3]. Knox et al [4] had reported the preparation of water-soluble Ferrocenyl sulfonic acid (SAFc) by sulphonation of ferrocene at the presence of reagent of chlorosulphonic acid in acetic anhydride.…”
mentioning
confidence: 99%
“…As far as know, most of the known ferrocenyl compounds are only soluble in hydrophobic media that limited their application in aqueous systems [2,3]. Knox et al [4] had reported the preparation of water-soluble Ferrocenyl sulfonic acid (SAFc) by sulphonation of ferrocene at the presence of reagent of chlorosulphonic acid in acetic anhydride.…”
mentioning
confidence: 99%